2017
DOI: 10.1002/2016gb005539
|View full text |Cite
|
Sign up to set email alerts
|

No long‐term trends in pCO2 despite increasing organic carbon concentrations in boreal lakes, streams, and rivers

Abstract: Concentrations of dissolved organic carbon (DOC) from terrestrial sources have been increasing in freshwaters across large parts of the boreal region. According to results from large‐scale field and detailed laboratory studies, such a DOC increase could potentially stimulate carbon dioxide (CO2) production, subsequently increasing the partial pressure of CO2 (pCO2) in freshwaters. However, the response of pCO2 to the presently observed long‐term increase in DOC in freshwaters is still unknown. Here we tested w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 93 publications
4
25
0
Order By: Relevance
“…Perhaps, the most interesting result is the strong negative control of P on p CO 2 . Although, previous large‐scale studies have found a positive relationship between P and open water p CO 2 (Rantakari & Kortelainen, ; Sobek et al., ), a recent temporal study over a 17‐year period found a negative or no relation at all between precipitation and p CO 2 in boreal inland waters (Nydahl, Wallin, & Weyhenmeyer, ). Nydahl et al.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Perhaps, the most interesting result is the strong negative control of P on p CO 2 . Although, previous large‐scale studies have found a positive relationship between P and open water p CO 2 (Rantakari & Kortelainen, ; Sobek et al., ), a recent temporal study over a 17‐year period found a negative or no relation at all between precipitation and p CO 2 in boreal inland waters (Nydahl, Wallin, & Weyhenmeyer, ). Nydahl et al.…”
Section: Discussionmentioning
confidence: 89%
“…Nydahl et al. () suggested that increased precipitation results in a dilution of CO 2 concentrations in inland waters due to an altered balance between surface and CO 2 ‐rich groundwater flow. In addition, P induced increased surface water runoff can cause a faster water flushing through the landscape giving less time for in situ CO 2 production in inland waters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After river discharge had peaked in April and May, both CO 2 and DIC concentrations at the river mouth showed a considerable decrease of ~ 50%, compared to the values obtained in March, which was probably related to a dilution effect during snowmelt and to decreased DIC export from soils (Kokic et al ). DOC concentrations at the river mouth, in contrast, did not differ between seasons, which might be explained by the fact that DIC and DOC can be exported from different soil horizons during varying runoff conditions (Giesler et al ; Nydahl et al ). However, despite the difference in DOC and DIC changes, both their spatial gradients reveal the path of river intrusion up to 15 km past the bay area in early June.…”
Section: Discussionmentioning
confidence: 97%
“…Limited direct p CO 2 observations combined with a growing interest in assessing a role of freshwaters in regional and global scales have resulted in studies relying on routinely measured CO 2 ‐related parameters to estimate p CO 2 and carbon flux from inland waters at global (Aufdenkampe et al, ; Cole et al, ; Cole et al, ; Raymond et al, ; Tranvik et al, ) and regional scales (Buffam et al, ; Butman & Raymond, ; Lapierre et al, ; McDonald et al, ) and evaluating temporal trends of inorganic carbon species (Jones et al, ; Nydahl, Wallin, & Weyhenmeyer, ; Seekell & Gudasz, ). We demonstrate, however, that field measurements of pH, ALK, and DIC might be insufficient to provide robust estimates of mean p CO 2 and question if they are sensitive enough to detect long‐term change in chemically heterogeneous lakes (Figures and and Table ).…”
Section: Discussionmentioning
confidence: 99%